Education, nationalism, cosmopolitanism: Toward a cosmopolitan public school - Valle, Lilian do (Education Policy Analysis Archives, 2019)
In its recent presidential campaign, Brazil witnessed the strength of the nationalist appeal, which has been gaining ground on the international scene in the face of the insecurity and frustration in which successive crises plunge societies. As diverse as expressions of nationalism are currently and historically since modernity, a common point between them is the intention to make education, and more particularly, the public school, a privileged instrument of its proselytism. Given the risks that this new withdrawal in an imagined identity announces, would the proposal of a cosmopolitanism be an adequate and viable response? On the basis of the criticism of this modern school, this article proposes the possibility of thinking of a “cosmopolitan school”.